Aerodynamic Effects of High-Speed Train Positions During Tunnel Exit Under Crosswind Conditions Using Computational Fluid Dynamics - Rajendran, S; Ishak, I. A; Arafat, M; Mohammad, A. F; Salleh, Z. M; Samiran, N. A; Ja’a, M. N. M; Sulaiman, S (UMP, 2024)
Strong crosswinds can cause catastrophic accidents like overturning and derailment in extreme circumstances, therefore the train's capacity to tolerate their impacts is crucial. Despite the significance of this issue, there exists a notable research gap in understanding the specific effects of various positions of a high-speed train within a tunnel on its aerodynamic loads and flow structure under different crosswind conditions. To address this gap, numerical simulations were performed using computational fluid dynamics. The crosswind angles (Ψ) were 15°, 30°, 45°, and 60° and the number of coaches exiting the tunnel was one to three coaches, respectively. The incompressible flow around the train was simulated using the Unsteady Reynolds Averaged NavierStokes (URANS) equations in conjunction with the k-epsilon (k-ε) turbulence model. The Reynolds number employed in the simulation was 1.3 x 106 , calculated based on the height of the train and the freestream velocity. With regard to aerodynamic performance due to the crosswind, force coefficients such as drag, side, and lift and moment coefficients of rolling, pitching, and yawing were measured. The higher crosswind angles including ψ = 45° and ψ = 60° cases produced the worse results of aerodynamic load coefficients compared to the lower crosswind angles of ψ = 15° and ψ = 30°. For instance, the highest side force coefficient (Cs) was recorded at a crosswind angle of ψ = 45°, with a value of 23.6. Meanwhile, the flow structure revealed that the leading coach of the train experienced intricate flow patterns during crosswinds, characterized by vortices and flow separation. These findings indicate that aerodynamic instabilities can potentially affect the overall performance of the train. Additionally, this increases the risk of derailment or overturning to be high, particularly when the majority of coaches are exiting the tunnel under strong crosswind conditions.